2017
DOI: 10.1017/jan.2017.10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation of organic minerals on the performance of broiler chicks fed oxidised soybean oil

Abstract: SummaryThe oxidation (rancidity) of fat is a very common feed quality issue, which can negatively affect growth performance and meat quality of broilers. Besides other factors, metal ions such as Zn, Cu and Fe can facilitate lipid peroxidation in feed. The objective of the current study was to investigate the effect of feeding corn soy diets containing fresh or oxidised soybean oil with different forms of microminerals on production performance of broiler chicks. Dietary treatments consisted of a 2 × 2 factori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
4
2
1
Order By: Relevance
“…Based on this information, experiment 1 was conducted to confirm the association between oxidized fat as a source of oxidative stress on the incidence of WB and evaluate the effect of proven nutritional antioxidant intervention. As expected, oxidized fat had an impact ( P < 0.05) on the performance of birds ( Table 3 ) in accordance with previous reports ( Dibner et al, 1996 ; Ao et al, 2017 ). A factorial analysis of live body weight for the effect of fat type showed that birds fed with oxidized fat (4.65 ± 0.04 kg) had lower ( P < 0.05) live weight than birds fed with fresh fat (4.82 ± 0.04 kg).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Based on this information, experiment 1 was conducted to confirm the association between oxidized fat as a source of oxidative stress on the incidence of WB and evaluate the effect of proven nutritional antioxidant intervention. As expected, oxidized fat had an impact ( P < 0.05) on the performance of birds ( Table 3 ) in accordance with previous reports ( Dibner et al, 1996 ; Ao et al, 2017 ). A factorial analysis of live body weight for the effect of fat type showed that birds fed with oxidized fat (4.65 ± 0.04 kg) had lower ( P < 0.05) live weight than birds fed with fresh fat (4.82 ± 0.04 kg).…”
Section: Resultssupporting
confidence: 92%
“…A factorial analysis of live body weight for the effect of fat type showed that birds fed with oxidized fat (4.65 ± 0.04 kg) had lower ( P < 0.05) live weight than birds fed with fresh fat (4.82 ± 0.04 kg). Previous studies have shown that presence of oxidized fat in the diet can destroy other nutrients in the diet matrix such as protein and fat-soluble vitamins ( Sheehy et al, 1994 ; Zdunczyk et al, 2002 ) and increase oxidative stress related damages in tissue ( Dibner et al, 1996 ) leading to reduced performance in broiler birds ( Ao et al, 2017 ). However, there were no effects ( P > 0.05) of oxidized fat on other carcass weight and yield parameters ( Table 3 ) in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of this, lower FCR values for ORM and COL diet groups throughout the growing period, specifically during the finisher diet phase were found. These results on FCR are in accordance with previous studies, stating that broiler chickens fed organic Ca, P, Cu, Fe, Mn, Zn had lower FCR levels (Nollet et al., 2007; Abdallah et al., 2009; Tahir et al., 2012; Oliveira et al., 2015; Ao et al., 2017) than broiler chickens fed inorganic mineral varieties, probably again due to the higher bio-availability of the ORM varieties.…”
Section: Discussionsupporting
confidence: 91%
“…At day 42, the chickens of the COL and ORM diet groups had a higher BW compared to the FISH diet group. The findings of the ORM diet group are in line with previous studies that showed that dietary organic sourced Ca and P (Tahir et al., 2012) and Cu, Fe, Mn, Zn (Bao et al., 2007; Abdallah et al., 2009; Ao et al., 2017) resulted in higher growth performance than their inorganic varieties, because of their functions in numerous biochemical reactions, increased bio-availability, and less antagonistic impact among each other. It can be speculated whether or not an increase of inorganic minerals compared to the current guidelines will result in comparable effects as when ORM are used.…”
Section: Discussionsupporting
confidence: 89%
“…Various natural resources, in particular zeolites, sapropels and mineral salts, play an interesting solution for increasing the productivity of farm animals and birds (Ao et al, 2017;Đuričić et al, 2017;Stankevica et al, 2016;Valpotić et al, 2017).…”
Section: Introductionmentioning
confidence: 99%